Manual reduction of jejunal intussusception in a poodle - Hawalia Limuja Putri Aditia; Sarwo Edy Wibowo; Vega Decline; Ahmad Syarifuddin; Yanita Mutiaraning Viastika; Jessica Anggun Safitri; Icha Yung Aulia; Pua Renoh Ajinasawor; Ida Tjahajati (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Jejunal intussusception is an uncommon cause of intestinal obstruction in dogs and is associated with abnormal motility, enteritis, parasitic infection, and foreign body ingestion. The diagnosis, surgical management, and outcome of a 3-year-old Poodle (5 kg) are described. The dog presented with vomiting, anorexia, weakness, abdominal pain, and foreign body ingestion. Abdominal radiography and hematology supported the diagnosis of intestinal obstruction and inflammatory response. Exploratory laparotomy confirmed jejunojejunal intussusception with congestion and hemorrhage without necrosis or perforation. The segment was reduced and repositioned without bowel resection or anastomosis. The abdominal wall was closed in layers, followed by postoperative therapy and monitoring, with wound healing by day 7 without complications.